Use of supplements by elite Japanese athletes in the PyeongChang 2018 Olympic Winter Games - Yoshino, M.; Yoshizaki, T.; Kondo, E.; Ishibashi, A.; Namma-Motonaga, K.; Kamihigashi, E.; Kamahara, K.; Kamei, A. (Journal of High Performance Sport, 2024)
Supplements are used to provide energy and nutrients that one's diet cannot adequately provide. There are also supplements for fatigue recovery and injury prevention. The Japan Institute of Sports Sciences (JISS) provides information on appropriate supplement use on its website. This information should be updated because the trend of using supplements among athletes varies depending on the market and the opinions of coaches, sporting event categories, age, and sex. Therefore, we aimed via this study to investigate supplement use among elite Japanese athletes.